Non-pathogenic bacteria elicit a differential cytokine response by intestinal epithelial cell/leucocyte co-cultures. Issue 1 (1st July 2000) - Haller, D; Bode, C; Hammes, W P; Pfeifer, A M A; Schiffrin, E J; Blum, S
Abstract : BACKGROUND AND AIM: Intestinal epithelial cells (IEC) are thought to participate in the mucosal defence against bacteria and in the regulation of mucosal tissue homeostasis. Reactivity of IEC to bacterial signals may depend on interactions with immunocompetent cells. To address the question of whether non-pathogenic bacteria modify the immune response of the intestinal epithelium, we co-cultivated enterocyte-like CaCO-2 cells with human blood leucocytes in separate compartments of transwell cultures. METHODS: CaCO-2/PBMC co-cultures were stimulated with non-pathogenic bacteria and enteropathogenic Escherichia coli . Expression of tumour necrosis factor alpha (TNF-α), interleukin (IL)-1β, IL-8, monocyte chemoattracting protein 1 (MCP-1), and IL-10 was studied by enzyme linked immunosorbent assays (cytokine secretion) and by semiquantitative reverse transcription-polymerase chain reaction. RESULTS: Challenge of CaCO-2 cells with non-pathogenic E coli and Lactobacillus sakei induced expression of IL-8, MCP-1, IL-1β, and TNF-α mRNA in the presence of underlying leucocytes. Leucocyte sensitised CaCO-2 cells produced TNF-α and IL-1β whereas IL-10 was exclusively secreted by human peripheral blood mononuclear cells. CaCO-2 cells alone remained hyporesponsive to the bacterial challenge. Lactobacillus johnsonii, an intestinal isolate, showed reduced potential to induce proinflammatory cytokines but increased transforming growth factor beta mRΝA in leucocyte sensitised CaCO-2 cells. TNF-α was identified as one of the early mediators involved in cellular cross talk. In the presence of leucocytes, discriminative activation of CaCO-2 cells was observed between enteropathogenic E coli and non-pathogenic bacteria. CONCLUSION: The differential recognition of non-pathogenic bacteria by CaCO-2 cells required the presence of underlying leucocytes. These results strengthen the hypothesis that bacterial signalling at the mucosal surface is dependent on a network of cellular interactions.